Method for preparing 5N grade copper raw material by chemical reduction combined with electrolytic purification
Patent Information
- Application Number
- CN202611460086.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-20
- Publication Date
- 2026-10-23
AI Technical Summary
[0008]本发明的目的在于,针对再生粗铜浸出液中砷、锑、铋、锡、铅等杂质含量高、直接电解无法获得5N级铜原料,且现有技术中能够直接产出5N级铜原料的工艺多从洁净铜料出发、难以适用于再生粗铜的缺陷,提供一种从从98.5%~99.5%品位的再生粗铜出发,在不进行区熔二次提纯、不使用硫化药剂的条件下直接获得Cu纯度不低于99.999%的5N级铜原料的方法
本发明以98.5%~99.5%品位的再生粗铜为起点,经两段差异化选择性还原将砷、锑与铋、锡、铅分步沉淀脱除,脱除率分别达到98.8%和99.1%以上,五类有害杂质的深度脱除在进入电解环节前即已完成,为电解提供了洁净基底;预处理全程不使用硫化钠或硫氢化钠,从源头根除硫化氢废气的产生,危废渣产量较同步硫化工艺减少约62%。电解环节的除杂负担因此集中于随浸出液带入的铁、镍离子:改性壳聚糖选择性络合亚铁离子和镍离子以提高二者的析出过电位,低电流密度、低温电解条件从动力学上抑制杂质放电,二者配合将铁和镍的单种杂质残留控制在0.09 ppm以下;稀土氯化物调控阳极泥形貌使其快速沉降,与旁路微滤循环相配合维持电解液洁净;结晶整平剂保障阴极铜结晶致密,减少电解液在沉积层中的滞留夹带。阴极铜再经多级超纯水超声洗涤脱除表面吸附的硫酸根和微量金属离子,并经真空低温干燥避免表面氧化,氧含量控制在0.5 ppm以下。整个流程无需区熔二次提纯,从再生粗铜浸出液直接获得Cu纯度不低于99.999%的5N级铜原料,铜直收率达到96.2%以上,电解残液补加药剂后返回调配工序循环使用,能够嵌入废杂铜直接制板的短流程,对多种再生原料均具有良好的适应性,为再生铜的高端化高值化利用提供了可行路径。
Smart Images

Figure CN122959533A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of hydrometallurgical refining and purification technology for non-ferrous metals, and more specifically, to a method for preparing 5N grade copper raw materials through chemical reduction combined with electrolytic purification. Background Technology
[0002] High-purity copper (5N grade, Cu purity not less than 99.999%) is a core basic material in high-end manufacturing fields such as semiconductor sputtering targets, integrated circuit lead frames, new energy current collectors, and vacuum electronic devices. These applications have extremely stringent requirements for controlling trace impurities; the content of any single harmful impurity—iron, tin, lead, bismuth, antimony, arsenic, and nickel—must be less than 0.1 ppm, and the total impurity content must be controlled within 10 ppm. Currently, the industrial production of high-purity copper mainly follows three technical routes, but each route has significant limitations.
[0003] The primary copper route mainly involves pyrometallurgical refining and electrolytic refining of copper concentrate to produce 4N grade (Cu≥99.99%) standard electrolytic copper. The inherent problem with this route is that harmful impurities such as arsenic, antimony, bismuth, and tin continuously accumulate during electrolyte circulation. Over long-term production, this leads to a continuous increase in cathode copper impurities, eventually stabilizing at only around 99.98%, which fails to meet the 5N grade standard.
[0004] The single electrolysis process for recycled crude copper is currently the most widely used low-cost route in the industry. Waste copper is melted and cast into anode plates using a simple pyrometallurgical process before direct electrolysis. However, in actual production, conventional single additives such as bone glue and thiourea can only improve the physical smoothness of the cathode crystals, but cannot effectively increase the overpotential for impurity deposition. Under high current density conditions, trace amounts of iron and nickel will co-deposit with copper, resulting in total impurities in the cathode copper generally exceeding 15 ppm. To achieve the 5N standard, an additional vacuum zone melting purification process is required. However, zone melting equipment is expensive, has extremely limited single-furnace capacity, and a single batch production cycle of over 72 hours, increasing the processing cost per ton of copper by approximately 4000 yuan, with copper volatilization losses as high as 2.5%. To avoid the zone melting process, existing technologies have also proposed a scheme to directly produce 5N-grade copper raw materials through a single electrolysis by optimizing the electrolyte system. This often uses clean copper materials such as 3N and 4N-grade copper as raw materials, combined with a pre-purified electrolyte, allowing 5N-grade copper raw materials to be obtained in a single electrolysis. However, such solutions require high-purity raw materials as a prerequisite, and impurity control is highly dependent on the purity of the raw materials themselves.
[0005] In the wet pretreatment stage, existing technologies mostly use sodium sulfide to simultaneously precipitate all heavy metal impurities. However, the sulfide precipitate particles are extremely fine, and the resulting flocculent particles can easily penetrate the filter medium, leading to trace amounts of lead and antimony ions remaining in the filtrate, which will still be co-deposited at the cathode during subsequent electrolysis. The simultaneous sulfidation process also easily generates highly toxic hydrogen sulfide gas, requiring significant investment in environmental remediation. Some alternative solutions, such as the 5N high-purity copper production method disclosed in Chinese invention patent application CN111378991A, use a nitric acid system for electrolysis, which suffers from severe equipment corrosion and the inability to achieve closed-loop electrolyte circulation.
[0006] The industry urgently needs a combined purification process that does not rely on secondary purification in zone melting, can operate stably on a large scale, and has controllable costs, so as to simultaneously achieve the ultimate removal of multiple types of trace harmful impurities and stably produce 5N grade copper raw materials.
[0007] In view of this, the present invention is proposed. Summary of the Invention
[0008] The purpose of this invention is to address the shortcomings of existing technologies that directly produce 5N grade copper raw materials, which are often made from recycled crude copper leaching solutions containing high levels of impurities such as arsenic, antimony, bismuth, tin, and lead, making it difficult to obtain 5N grade copper raw materials through direct electrolysis. Furthermore, existing technologies that can directly produce 5N grade copper raw materials often start from clean copper materials and are not applicable to recycled crude copper. This invention provides a method for directly obtaining 5N grade copper raw materials with a Cu purity of not less than 99.999% from recycled crude copper with a purity of 98.5% to 99.5%, without secondary purification through zone melting or the use of sulfiding agents.
[0009] This invention is implemented as follows: In a first aspect, the present invention provides a method for preparing 5N grade copper raw materials by chemical reduction combined with electrolytic purification, comprising the following steps: S1. Acid dissolution of crude copper: Take recycled crude copper anode material, leach it with dilute sulfuric acid, and separate the solid and liquid to obtain crude copper acid dissolution stock solution; S2, First stage selective reduction: Sulfite reducing agent is added to the crude copper acid solution to react, solid-liquid separation is performed, and arsenic and antimony are removed; S3, Second stage selective reduction: Add hypophosphite reducing agent to the filtrate obtained in S2 to react, separate solid and liquid, and remove bismuth, tin and lead; S4. Electrolyte preparation: Take the filtrate obtained in S3 as the base electrolyte, add composite selective additives to obtain composite electrolyte; The composite selective additive comprises modified chitosan, rare earth chloride, and crystallization leveling agent; S5, Low-temperature and low-current electrolysis: Using an insoluble anode, a pure copper cathode and the composite electrolyte prepared in S4, electrolysis is performed at a current density of 90-140 A / m² and a temperature of 42-50℃. The composite electrolyte is circulated through microfiltration. S6. Ultrasonic washing and drying: The cathode copper obtained by electrolysis is ultrasonically washed with multi-stage ultrapure water and then vacuum dried to obtain the 5N grade copper raw material.
[0010] In an optional embodiment, in S1, the recycled crude copper anode material is a scrap copper pyrometallurgical rough casting anode or intermediate crude copper material from copper smelting, with a Cu mass fraction of 98.5% to 99.5%.
[0011] In an optional embodiment, in S1, the concentration of the dilute sulfuric acid is 1.6–2.2 mol / L; And / or, the liquid-to-solid ratio of dilute sulfuric acid to recycled crude copper anode material is 5.5:1 to 7:1; And / or, the leaching temperature is 65–75°C.
[0012] In an optional embodiment, in S2, the molar ratio of the sulfite reducing agent to As and Sb in the crude copper acid solution is 1.8:1 to 2.4:1. In S3, the molar ratio of the hypophosphite reducing agent to Bi, Sn, and Pb in the filtrate obtained in S2 is 2.2:1 to 3.0:1.
[0013] In an optional embodiment, in S2, the reaction temperature is 40–48°C and the pH is 2.0–2.8; In S3, the reaction temperature is 45–53℃ and the pH is 3.2–4.0.
[0014] In an optional embodiment, in S4, the modified chitosan is carboxymethyl chitosan; And / or, the rare earth chloride is a mixture of lanthanum chloride and cerium chloride; the mass ratio of lanthanum chloride to cerium chloride is 2~4:2; And / or, the crystallization leveling agent is a mixture of an organic sulfonate containing thiol groups and / or disulfide bonds and low molecular weight gelatin.
[0015] In an optional embodiment, the concentration of modified chitosan in the composite selective additive is 0.02–0.06 g / L, the concentration of rare earth chloride is 0.008–0.018 g / L, and the concentration of crystallization leveling agent is 0.012–0.025 g / L.
[0016] In an optional embodiment, in S5, the electrolysis time is 22–32 h and the distance between the anode and cathode is 85–105 mm.
[0017] In an optional implementation, in S5, the electrolyte is circulated via a bypass 0.2 μm microfiltration; after electrolysis, the residual electrolyte is replenished with sulfuric acid and a composite selective additive and then returned to S4 for reuse.
[0018] In an optional embodiment, the 5N grade copper raw material has a Cu purity ≥ 99.999%, a total impurity content ≤ 10 ppm, a single impurity content of Fe, Sn, Pb, Bi, Sb, As, and Ni ≤ 0.09 ppm, an oxygen content ≤ 0.5 ppm, and a copper direct recovery rate ≥ 96.2%.
[0019] The present invention has the following beneficial effects: This invention starts with recycled crude copper of 98.5%–99.5% purity. Arsenic, antimony, bismuth, tin, and lead are removed stepwise through two stages of differentiated selective reduction, with removal rates reaching over 98.8% and 99.1%, respectively. The deep removal of these five types of harmful impurities is completed before entering the electrolysis stage, providing a clean substrate for electrolysis. Sodium sulfide or sodium hydrosulfide is not used throughout the pretreatment process, eliminating the generation of hydrogen sulfide waste gas at the source. The amount of hazardous waste residue is reduced by approximately 62% compared to the simultaneous sulfidation process. The burden of impurity removal in the electrolysis process is therefore concentrated on the iron and nickel ions introduced with the leachate: modified chitosan selectively complexes ferrous and nickel ions to increase their deposition overpotential; low current density and low-temperature electrolysis conditions kinetically suppress impurity discharge; the combination of these two methods controls the residual amount of single impurities of iron and nickel to below 0.09 ppm; rare earth chloride regulates the morphology of the anode mud to promote rapid sedimentation, and works in conjunction with bypass microfiltration circulation to maintain electrolyte cleanliness; a crystallization leveling agent ensures dense cathode copper crystals and reduces electrolyte retention and entrainment in the deposition layer. The cathode copper is then subjected to multi-stage ultrasonic washing with ultrapure water to remove adsorbed sulfate and trace metal ions from the surface, and vacuum low-temperature drying to prevent surface oxidation, with the oxygen content controlled below 0.5 ppm. The entire process does not require secondary purification through zone melting. It directly obtains 5N grade copper raw materials with a Cu purity of not less than 99.999% from the recycled crude copper leaching solution, with a direct copper recovery rate of over 96.2%. The residual electrolytic solution is returned to the blending process for recycling after the addition of reagents. It can be integrated into a short process for direct plate making from scrap copper and has good adaptability to various recycled raw materials, providing a feasible path for the high-end and high-value utilization of recycled copper. Attached Figure Description
[0020] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0021] Figure 1 This is a flowchart illustrating the overall process for preparing 5N grade copper raw materials through a combination of chemical reduction and electrolytic purification. Detailed Implementation
[0022] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0023] Firstly, such as Figure 1 As shown, this invention provides a method for preparing 5N grade copper raw materials through chemical reduction combined with electrolytic purification, comprising the following steps: S1. Acid dissolution of crude copper: Take recycled crude copper anode material, leach it with dilute sulfuric acid, and separate the solid and liquid to obtain crude copper acid dissolution stock solution; S2, First stage selective reduction: Sulfite reducing agent is added to the crude copper acid solution to react, solid-liquid separation is performed, and arsenic and antimony are removed; S3, Second stage reduction: Add hypophosphite reducing agent to the filtrate obtained in S2 to react, separate solid and liquid, and remove bismuth, tin and lead; S4. Electrolyte preparation: Take the filtrate obtained in S3 as the base electrolyte, add composite selective additives to obtain composite electrolyte; The composite selective additive comprises modified chitosan, rare earth chloride, and crystallization leveling agent; S5, Low-temperature and low-current electrolysis: Using an insoluble anode, a pure copper cathode and the composite electrolyte prepared in S4, electrolysis is performed at a current density of 90-140 A / m² and a temperature of 42-50℃. The composite electrolyte is circulated through microfiltration. S6. Ultrasonic washing and drying: The cathode copper obtained by electrolysis is ultrasonically washed with multi-stage ultrapure water and then vacuum dried to obtain the 5N grade copper raw material.
[0024] This invention employs a two-stage differentiated chemical reduction pretreatment. Sulfite-based reducing agents selectively reduce high-valence ions of arsenic and antimony (As(V) and Sb(V)) under low pH and low temperature conditions, converting them into low-solubility elemental or arsenite precipitates. This is combined with the directional precipitation of bismuth, tin, and lead hydroxide composite precipitates by hypophosphite-based reducing agents in a weakly acidic system, achieving the graded and deep removal of seven types of harmful impurities. Compared to traditional simultaneous sulfidation precipitation, this stepwise differentiated strategy avoids the generation of hydrogen sulfide gas and significantly reduces copper entrainment loss in the reduction slag. Subsequent use of a ternary composite additive electrolyte system containing modified chitosan, rare earth chlorides, and a crystallization leveling agent further enhances the process. Modified chitosan selectively complexes ferrous and nickel ions, significantly increasing the overpotential for the precipitation of these two impurities. Rare earth chlorides optimize the morphology of the anode mud, reducing the drift of suspended impurities in the electrolyte. The crystallization leveling agent ensures a dense, pinhole-free cathode copper deposition layer. Low-temperature, low-current-density electrolysis kinetically weakens the diffusion and migration of impurity ions, thus inhibiting impurity co-deposition at the source. Multi-stage ultrapure water ultrasonic cleaning combined with vacuum low-temperature drying completely removes trace amounts of sulfate and metal ions adsorbed on the cathode surface, ultimately yielding 5N-grade copper raw material.
[0025] In an optional embodiment, in S1, the recycled crude copper anode material is a scrap copper pyrometallurgical rough casting anode or intermediate crude copper material from copper smelting, with a Cu mass fraction of 98.5% to 99.5%.
[0026] In an optional embodiment, in S1, the concentration of the dilute sulfuric acid is 1.6 to 2.2 mol / L.
[0027] In an optional embodiment, the liquid-to-solid ratio of dilute sulfuric acid to recycled crude copper anode material is 5.5:1 to 7:1.
[0028] In an optional embodiment, Cu in the crude copper acid dissolution solution 2+ The concentration is 56–72 g / L.
[0029] Cu 2+ It also affects the current efficiency, deposition rate, and solution stability of electrolysis. Cu 2+ At low concentrations, the concentration polarization at the cathode surface increases, the limiting current density decreases, and the electrolysis process easily enters the diffusion control region. This not only reduces current efficiency but also makes it easier for impurity ions to co-deposit at the cathode discharge. 2+ When the concentration is too high, copper sulfate approaches its saturation solubility. Temperature fluctuations or acidity disturbances during production may cause copper sulfate to crystallize and precipitate. If the crystal particles enter the circulation pipeline, they will cause blockage. If they are suspended in the electrolyte, they will become a source of cathode contamination.
[0030] During the leaching process with dilute sulfuric acid, hydrogen ions dissolve the copper matrix and simultaneously dissolve various impurities. Therefore, controlling the acidity and the solid-liquid ratio of the sulfuric acid solution to the recycled crude copper anode material can control the copper ion concentration and regulate the leaching rate. When the sulfuric acid concentration is too low, the leaching driving force is insufficient, resulting in a significant decrease in the leaching rate and incomplete copper leaching. Undissolved copper is discharged with the residue, directly eroding the copper recovery rate. While a higher concentration can accelerate leaching, it also exacerbates equipment corrosion and increases the consumption of pH adjustment in subsequent processes. Furthermore, if the liquid-to-solid ratio of the sulfuric acid solution is too low, the slurry becomes viscous, making it difficult for the acid to penetrate evenly within the material layer, leading to insufficient leaching in localized areas. Simultaneously, the high viscosity of the slurry increases the amount of filtrate entrained in the filter cake during pressure filtration, raising the risk of impurities being carried into the next process. While a high liquid-to-solid ratio is beneficial for dispersion, it simultaneously increases equipment volume and acid consumption. Moreover, the diluted copper ion concentration of the leachate is insufficient to meet electrolysis requirements, thus increasing the burden on subsequent concentration processes.
[0031] In an optional embodiment, the leaching temperature is 65–75°C.
[0032] In an optional implementation, the leaching is performed at a constant temperature.
[0033] Leaching temperature also affects the leaching rate and the equilibrium concentration of copper sulfate. When the temperature is too low, the leaching reaction rate is slow, and the stirring time needs to be significantly extended to achieve the same leaching rate, thus limiting production capacity; when the temperature is too high, the solubility of copper sulfate decreases, and the precipitated basic copper sulfate will adhere to the surface of the residue and carry away copper.
[0034] In some implementations, by combining the parameters of the above leaching process, a concentration window of 1.6 to 2.2 mol / L with a leaching temperature of 65 to 75°C and a liquid-solid ratio of 5.5:1 to 7:1, the leaching can reach equilibrium within a stirring time of 2.5 to 3.5 h.
[0035] In an optional embodiment, in S2, the molar ratio of the sulfite reducing agent to As and Sb in the crude copper acid solution is 1.8:1 to 2.4:1.
[0036] Arsenic and antimony in the crude copper acid dissolution solution mainly exist in the high-valence states of As(V) and Sb(V). Their ionic forms have high solubility in sulfuric acid systems and are difficult to separate directly. Among sulfite reducing agents, sulfur is in the +4 valence state and has strong reducing properties in acidic media, reducing As(V) and Sb(V) to As(III) and Sb(III), which then precipitate out as low-soluble elements or arsenite, and are removed through solid-liquid separation. Based on the total amount of As and Sb in the raw solution: if the ratio of sulfite reducing agent is less than 1.8:1, the reducing agent is insufficient to fully convert the high-valence arsenic and antimony, and the residual arsenic and antimony in the filtrate will exceed 0.0015 g / L. The residual As and Sb will co-deposit at the cathode after entering the subsequent electrolysis process, directly increasing the single impurity index of the finished product. Conversely, if the ratio is greater than 2.4:1, excess sodium bisulfite will further reduce the Cu in the solution. 2+ to convert it into Cu + Even copper powder entering the reduction slag can cause a decrease in the direct copper recovery rate. Therefore, the ratio is controlled at 1.8:1 to 2.4:1 to ensure that the removal rate of As and Sb reaches more than 98.8% and the filtrate residue is ≤0.0015 g / L, while keeping the copper reduction loss to a negligible level.
[0037] In an optional embodiment, the sulfite reducing agent includes one or both of sodium bisulfite and potassium bisulfite.
[0038] In an optional embodiment, in S2, the reaction temperature is 40–48°C and the pH is 2.0–2.8.
[0039] In an optional embodiment, in S2, high-valence As and Sb ions are reduced to low-solubility elements and / or arsenite precipitates.
[0040] The reducing activity of sulfite reducing agents is closely related to the system temperature. When the temperature is low, the reduction reaction rate of As(V) and Sb(V) slows down significantly. To achieve the same removal rate, the time must be greatly extended, which affects the production capacity. When the temperature is high, the tendency of sulfite reducing agents (such as sodium bisulfite) to thermally decompose in aqueous solution is intensified. The sulfur dioxide released by decomposition not only reduces the effective utilization rate of the reducing agent, but also forms a sulfur-containing atmosphere in the system.
[0041] The forms of arsenic and antimony in solution change with pH. Their higher-valence ions show a stronger thermodynamic tendency to be reduced by sodium bisulfite under acidic conditions, and the reduction products (elemental or arsenite) have lower solubility in the acidic range, which is conducive to complete precipitation. Meanwhile, copper hydroxide begins to form above weakly acidic conditions. If the pH is too high, copper will enter the slag phase as a hydrolysis product, resulting in loss. Below pH 2.0, excessive acidity increases the tendency for reduction products to redissolve, thus decreasing the removal rate. Above pH 2.8, the risk of copper hydrolysis loss and incomplete precipitation of arsenic and antimony increases simultaneously.
[0042] In an optional embodiment, in S2, pressure filtration is performed to reduce the residual arsenic and antimony in the filtrate to ≤0.0015 g / L.
[0043] In an optional embodiment, in S3, the molar ratio of the hypophosphite reducing agent to Bi, Sn, and Pb in the filtrate obtained in S2 is 2.2:1 to 3.0:1.
[0044] In an optional embodiment, the hypophosphite reducing agent includes one or both of sodium hypophosphite and potassium hypophosphite.
[0045] In an optional embodiment, in S3, Bi, Sn, and Pb ions are reduced to form a sparingly soluble metal hydroxide complex precipitate.
[0046] Bismuth, tin, and lead precipitate differently in weakly acidic systems than arsenic and antimony. Hypophosphite reducing agents react with Bi in the weakly acidic range of pH 3.2–4.0. 3+ Sn 2+ / Sn 4+ Pb 2+ Its function is to generate a sparingly soluble metal hydroxide complex precipitate phase (accompanied by phosphate precipitate products), thereby achieving the targeted removal of three types of impurities. The dosage is based on the total amount of Bi, Sn, and Pb in the filtrate: when the ratio is less than 2.2:1, the precipitant is insufficient to completely convert the three types of ions, and the residual Bi, Sn, and Pb will co-deposit at the cathode after entering the electrolysis process, directly damaging the copper purity index; when the ratio is greater than 3.0:1, excessive hypophosphite introduces phosphorus into the system, and residual phosphorus contaminates the electrolyte and may enter the cathode copper.
[0047] In an optional embodiment, the reaction temperature is 45–53°C and the pH is 3.2–4.0.
[0048] Temperature and pH both affect the precipitation of Bi, Sn, and Pb. When the temperature is too low, the precipitation conversion rate of Bi, Sn, and Pb is slow, requiring an excessively long reaction time. When the temperature is too high, the already formed tin and lead hydroxide precipitates show a tendency to dissolve back, and the removal rate decreases instead of increasing. In addition, the precipitation of Bi, Sn, and Pb hydroxides are all in the weakly acidic range. Under pH conditions of 3.2 to 4.0, the precipitation of Bi, Sn, and Pb ions is complete. When the pH is below 3.2, the precipitation will be incomplete. However, the pH at which copper begins to hydrolyze is higher than this window, and the hydrolysis of copper is effectively inhibited. Therefore, the precipitation process results in almost no loss of copper.
[0049] In an optional implementation, in step S3, a two-stage precision membrane pressure filtration separation is performed, and the filtrate contains Bi ≤ 0.0008 g / L, Sn ≤ 0.0006 g / L, and Pb ≤ 0.0009 g / L.
[0050] In an optional embodiment, in S4, the modified chitosan is a chitosan with hydroxyl and amino groups.
[0051] Chitosan contains hydroxyl and amino groups, giving it a natural ability to coordinate with transition metal ions. However, it has poor water solubility under neutral and alkaline conditions, making it difficult to disperse evenly and resulting in low complexation efficiency when used directly as an electrolytic additive. After modification, the complexation activity of the amino and hydroxyl groups in acidic electrolytes is fully utilized, enabling selective complexation with Fe. 2+ Ni 2+ The formation of stable complexes significantly increases the deposition overpotential of these two impurities, thereby enabling them to be transported to copper ions in cathode competition and making co-deposition difficult.
[0052] In an optional embodiment, the modified chitosan is carboxymethyl chitosan.
[0053] In an optional embodiment, the rare earth chloride is a mixture of lanthanum chloride and cerium chloride; the mass ratio of lanthanum chloride to cerium chloride is 2~4:2; preferably 3:2.
[0054] Anode sludge, generated from oxygen evolution on the insoluble anode surface during electrolysis, is a major source of suspended contamination, and its morphology and sedimentation behavior directly affect the cleanliness of the electrolyte. The composite system of lanthanum chloride and cerium chloride modulates the morphological characteristics of the anode sludge, making the sludge particles easier to settle and significantly reducing suspended drift, thereby lowering the probability of suspended particles being trapped on the cathode surface. However, the effect of a single rare earth element is insufficient, and the final product cannot achieve a purity of 5N. Furthermore, this application found a synergistic window in the mass ratio of the two rare earth elements: when the lanthanum content is too low, the anode sludge lacks dispersibility and is prone to caking; when the lanthanum content is too high, the anode sludge becomes overly dispersed, leading to new suspended contamination.
[0055] In an optional embodiment, the crystallization leveling agent is a mixture of an organic sulfonate containing thiol groups and / or disulfide bonds and low molecular weight gelatin.
[0056] In the crystallization leveling agent, the thiol groups or disulfide bonds in the organic sulfonate molecules containing thiol and / or disulfide bonds can strongly interact with copper ions or the cathode copper surface, reducing electrochemical polarization and promoting the preferential deposition of copper ions in microscopic depressions. Simultaneously, it induces the formation of new crystal nuclei, thereby refining the grains and improving the brightness of the deposited layer. Low-molecular-weight gelatin acts as both a leveling agent and an inhibitor. Its long-chain macromolecules preferentially adsorb onto microscopic protrusions and tips with high electric field strength on the cathode surface, forming an isolation layer to suppress the copper deposition rate in these areas, allowing copper ions to replenish the deposition in the depressions, thus achieving macroscopic surface smoothing. The two agents complement each other to produce a synergistic effect: organic sulfonates promote grain refinement and microscopic filling, while gelatin inhibits excessive protrusion growth and improves the dispersion ability of the electrolyte. Ultimately, a dense, uniformly grained, and smooth cathode copper deposited layer is obtained, effectively improving the quality and efficiency of electrolytic copper purification.
[0057] Preferably, the organic sulfonate containing thiol groups and / or disulfide bonds includes one or more of sodium polydithiopropane sulfonate, sodium 3-mercaptopropane sulfonate, and 3,3'-dithiopropane sulfonic acid; more preferably, sodium polydithiopropane sulfonate.
[0058] In an optional embodiment, the mass ratio of the organic sulfonate containing thiol groups and / or disulfide bonds to the low molecular weight gelatin is 1:1 to 10, preferably 1:5.
[0059] When the proportion of sodium polydisulfide dipropane sulfonate (SPS) in the crystallization leveling agent is too high (below 1:3), the adsorption is too strong, the internal stress of the deposited layer increases and it becomes brittle, and SPS contains sulfur, so excessive use poses a risk of sulfur inclusions; when the proportion of gelatin is too high (above 1:8), the adsorption layer is too thick, which leads to excessive crystallization and thus coarsness.
[0060] In an optional embodiment, the modified chitosan concentration in the electrolyte is 0.02–0.06 g / L, the rare earth chloride concentration is 0.008–0.018 g / L, and the crystallization leveling agent concentration is 0.012–0.025 g / L.
[0061] In the composite selective additives, modified chitosan is responsible for complexing Fe / Ni, rare earth chlorides are responsible for regulating anode mud, and crystallization leveling agents are responsible for dense crystallization. Among them, when the concentration of modified chitosan is below 0.02 g / L, the complexing capacity is insufficient, and Fe / Ni co-deposition re-emerges. When it is above 0.06 g / L, the solution viscosity increases, and excessive adsorption on the cathode surface makes the crystals rough. When the concentration of rare earth chloride is below 0.008 g / L, the morphology regulation of anode mud fails and it is prone to caking. When it is above 0.018 g / L, the anode mud is excessively dispersed, forming suspended pollution. When the concentration of crystallization leveling agent is below 0.012 g / L, the crystals are loose and pinholes are generated. When it is above 0.025 g / L, the brittleness of the cathode increases.
[0062] In an optional embodiment, the sulfuric acid concentration in the composite electrolyte is 1.4–2.0 mol / L.
[0063] The sulfuric acid in the electrolyte acts as a conductive medium and reacts with Cu. 2+ The stabilizer plays a dual role: insufficient acidity leads to decreased electrolyte conductivity, increased cell voltage, and increased energy consumption; furthermore, Cu... 2+ At low acidity, it tends to hydrolyze, which compromises the stability of the solution; when the acidity is too high, the anodic oxygen evolution reaction intensifies, the consumption of the titanium-based oxide coating accelerates, and the stability of the additives is also affected.
[0064] In an optional implementation, after S4, trace amounts of suspended colloids are removed by filtration.
[0065] In an optional embodiment, in S5, the insoluble anode is a titanium-based noble metal oxide coated anode.
[0066] Preferably, the insoluble anode is one of titanium-coated ruthenium anode, titanium-coated iridium anode, titanium-coated ruthenium-iridium composite anode, titanium-coated iridium-tantalum composite anode, and titanium-coated platinum anode; more preferably, it is a titanium-coated ruthenium anode.
[0067] In an optional embodiment, in S5, the electrolysis time is 22–32 h and the distance between the anode and cathode is 85–105 mm.
[0068] In pursuit of increased production capacity, the copper electrolysis industry commonly employs high current densities of 240-300 A / m². However, at these high current densities, concentration polarization at the cathode surface increases, leading to Fe... 2+ Ni 2+ The discharge tendency of impurity ions is amplified, making co-deposition difficult to avoid; this application reduces the current density to 90~140 A / m. 2 At low current densities, the deposition rate of copper ions is moderate, and the cathode surface always maintains a low overpotential. The Fe / Ni deposition overpotential is maintained, and impurity ions lose the opportunity for co-deposition kinetically.
[0069] Electrolysis time and current density together determine the thickness and yield of the deposited layer. In this application, when using a low current density, the electrolysis time is adjusted to 22-32 h. If the electrolysis time is too short, the deposited layer thickness will be insufficient, the yield per cell will be low, and the peeling will be difficult. If the time is too long, the cathode surface will be exposed to the electrolyte for a long time, and the risk of impurity enrichment and secondary inclusion will increase as the deposited layer thickens.
[0070] In an optional implementation, in S5, the electrolyte is circulated via a bypass 0.2 μm microfiltration.
[0071] During electrolysis, anode sludge and suspended particles are continuously generated. If not removed in time, these particles will adhere to the cathode surface during electrolyte flow, becoming inclusions in the deposition layer. The bypass 0.2 μm microfiltration circulation ensures that the electrolyte continuously passes through the filtration circuit, continuously intercepting suspended particles and maintaining the cleanliness of the electrolyte over a long period.
[0072] In an optional implementation, in S5, the electrolysis process is carried out in a closed negative pressure environment to prevent the introduction of oxygen impurities through air oxidation.
[0073] In an optional implementation, the anode-cathode area ratio is 1:1 to 1:1.2.
[0074] Under the premise of constant total current, an anode area larger than the cathode means that the anode current density is lower than the cathode current density, resulting in a more gradual oxygen evolution reaction. This reduces the consumption of the titanium-based noble metal oxide coating under high current density, extending the anode's service life. It also reduces the formation rate of anode sludge and minimizes the disturbance and entrainment of anode sludge by escaping oxygen bubbles, making the anode sludge settle more easily. Combined with bypass microfiltration, this maintains electrolyte cleanliness. When the ratio is too small (below 1.02), the anode current density approaches the cathode current density, intensifying oxygen evolution. Coating consumption and anode sludge formation increase simultaneously, increasing the risk of suspended contamination. When the ratio is too large (above 1.15), the anode occupies more space in the cell, increasing equipment investment and reducing the effective volume utilization rate of the electrolytic cell. Furthermore, current concentration and uneven deposition layer thickness are more likely to occur at the cathode edge.
[0075] Preferably, the anode-cathode area ratio is 1:1.02~1.15, and more preferably 1:1.05.
[0076] In an optional implementation, the electrode spacing is 85–105 mm.
[0077] The electrode spacing determines the electric field distribution and cell voltage level within the electrolytic cell. When the electrode spacing is too small, the electric field distribution between the anode and cathode is uneven, the edge effect is amplified, the deposition layer thickness is uneven, and short circuits between electrodes are prone to occur. When the electrode spacing is too large, the solution resistance increases, the cell voltage rises, and the power consumption per ton of copper increases.
[0078] In an optional implementation, after electrolysis is completed, the crude copper deposited at the cathode is stripped off.
[0079] In an optional embodiment, in S6, the crude cathode copper is ultrasonically cleaned with grade 4 ultrapure water for 6-10 minutes with a power of 180-240 W; during vacuum drying, the vacuum degree is ≤0.008 MPa, and the drying temperature is 65-75℃ for 90-130 minutes, and then cooled to obtain 5N grade copper raw material.
[0080] Electrolytically deposited cathode copper inevitably adsorbs sulfate ions and trace metal ions from the electrolyte onto its surface. If these surface residues are not removed, they will be directly included in the impurity content of the finished product. Multi-stage ultrapure water ultrasonic cleaning utilizes ultrasonic cavitation to enhance surface desorption; the four-stage cleaning progressively dilutes and removes the adsorbed layer. If the single-stage time is too short or the power is insufficient, desorption is incomplete, and surface residues increase the total impurity content. If the time is too long or the power is too high, ultrasonic vibration may cause copper powder to detach from the surface, increasing losses. After cleaning, residual moisture remains on the cathode copper surface. If the drying process is carried out at high temperatures in air, the copper surface will oxidize, resulting in excessive oxygen content. Vacuum low-temperature drying utilizes negative pressure to lower the boiling point of water, completing moisture removal at a low temperature of 65-75℃. No oxygen is involved throughout the process, fundamentally avoiding the risk of oxidation. Insufficient vacuum, excessively high temperature, or excessively short time will all lead to incomplete drying or surface oxidation.
[0081] In an optional implementation, in S6, the resistivity of the ultrapure water is ≥18.2 MΩ·cm, and the temperature of the single-stage cleaning water is 30~38℃.
[0082] In an optional implementation, S7 is also included: after electrolysis is completed, the residual electrolyte is replenished with sulfuric acid and a composite selective additive and then returned to S4 for reuse.
[0083] In an optional implementation, the filter residue obtained from the solid-liquid separation in S2 and S3 is used for valuable metal recovery.
[0084] In an optional embodiment, the 5N grade copper raw material has a Cu purity ≥ 99.999%, a total impurity content ≤ 10 ppm, a single impurity content of Fe, Sn, Pb, Bi, Sb, As, and Ni ≤ 0.09 ppm, an oxygen content ≤ 0.5 ppm, and a copper direct recovery rate ≥ 96.2%.
[0085] The features and performance of the present invention will be further described in detail below with reference to embodiments.
[0086] Example 1 This embodiment provides a method for preparing 5N grade copper raw materials through chemical reduction combined with electrolytic purification, including: S1. Preparation of crude copper acid leaching solution: Regenerated crude copper anode material with a Cu mass fraction of 98.5% was selected and leached at a constant temperature of 65℃ with 1.6 mol / L sulfuric acid at a liquid-to-solid ratio of 5.5:1. The mixture was stirred for 2.5 hours and then filtered to obtain a Cu-containing solution. 2+ 58 g / L, impurities Fe0.06 g / L, Sn 0.02 g / L, Pb 0.03 g / L, Bi 0.015 g / L, Sb 0.012 g / L, As 0.04 g / L, Ni0.05 g / L.
[0087] S2, First stage reduction: Sodium bisulfite to total arsenic to total antimony molar ratio 1.8:1, pH 2.0, react at 40℃ for 110 min, and after pressure filtration, As and Sb ≤ 0.0015 g / L.
[0088] S3, Second stage reduction: Sodium hypophosphite is reacted with Bi+Sn+Pb in a molar ratio of 2.2:1 at pH 3.2 at 45℃ for 130 min. After filtration through a precision membrane, Bi ≤ 0.0008 g / L, Sn ≤ 0.0005 g / L, and Pb ≤ 0.0006 g / L.
[0089] S4. Electrolyte preparation: modified chitosan 0.02 g / L, rare earth chloride (lanthanum chloride: cerium chloride = 3:2, mass ratio) 0.008 g / L, crystallization leveling agent 0.012 g / L, sulfuric acid acidity 1.4 mol / L, 0.2 μm microfiltration.
[0090] S5. Electrolysis: Titanium-coated ruthenium anode, pure copper cathode, anode-cathode area ratio of 1:1.05, electrode spacing of 85 mm, constant temperature of 42℃, current density of 90 A / m², electrolysis for 22 h, closed negative pressure microfiltration circulation.
[0091] S6. Ultrasonic drying: Grade 4 ultrapure water ultrasonic cleaning, single stage 6 min, power 180 W, vacuum 0.008 MPa, drying at 65℃ for 90 min.
[0092] The results showed that the Cu purity was 99.9993%, the total impurities were 7 ppm, the single harmful impurity was ≤0.072 ppm, and the direct copper recovery rate was 96.2%.
[0093] Example 2 A method for preparing 5N grade copper raw materials by chemical reduction combined with electrolytic purification, comprising the following steps: S1. Preparation of crude copper acid leaching solution: Regenerated crude copper anode material with a Cu mass fraction of 98.7% was selected, sulfuric acid concentration was 1.7 mol / L, leaching temperature was 67℃, liquid-to-solid ratio was 5.8:1, and stirring was carried out for 2.7 h; the Cu in the solution was then pressed. 2+61 g / L, impurities Fe 0.09 g / L, Sn0.04 g / L, Pb 0.05 g / L, Bi 0.028 g / L, Sb 0.021 g / L, As 0.07 g / L, Ni 0.07 g / L.
[0094] S2, one-stage reduction to remove arsenic and antimony: sodium bisulfite molar ratio 1.9:1, pH 2.1, reaction at 41℃ for 118 min, after pressure filtration to remove residue, As and Sb ≤ 0.0015 g / L.
[0095] S3, Two-stage reduction of bismuth, tin and lead: Sodium hypophosphite molar ratio 2.3:1, pH 3.3, reaction at 46℃ for 138 min, precision membrane pressure filtration, Bi≤0.0008 g / L, Sn≤0.0004 g / L, Pb≤0.0005 g / L.
[0096] S4. Electrolyte preparation: modified chitosan 0.025 g / L, rare earth chloride (lanthanum chloride: cerium chloride = 3:2, mass ratio) 0.010 g / L, crystallization leveling agent 0.014 g / L, sulfuric acid acidity 1.5 mol / L.
[0097] S5. Electrolysis: Titanium-coated ruthenium anode, pure copper cathode, electrode spacing 90 mm, constant temperature 43℃, current density 100 A / m², electrolysis for 24 h, closed microfiltration circulation.
[0098] S6. Ultrasonic drying: ultrasonic power 190 W, single stage for 7 min, vacuum drying at 67℃ for 98 min.
[0099] S7: Metal is recovered from the reduction slag, and the electrolyte is recycled.
[0100] The results showed that Cu content was 99.9992%, total impurities were 8 ppm, the highest single impurity was 0.074 ppm, and the direct recovery rate was 96.4%.
[0101] Example 3 A method for preparing 5N grade copper raw materials by chemical reduction combined with electrolytic purification, comprising the following steps: S1. Preparation of crude copper acid leaching solution: 98.9% Cu crude copper, 1.8 mol / L sulfuric acid, leaching at 68℃, liquid-to-solid ratio 6:1, stirring for 2.8 h, original solution Cu² + 63 g / L, Fe 0.11 g / L, Sn 0.06 g / L, Pb 0.07 g / L, Bi 0.042 g / L, Sb0.033 g / L, As 0.10 g / L, Ni 0.09 g / L.
[0102] S2, First stage reduction: Sodium bisulfite ratio 2.0:1, pH 2.2, reaction at 42℃ for 125 min, filter press to separate the residue, after filtration As and Sb ≤ 0.0015 g / L.
[0103] S3, Two-stage reduction: Sodium hypophosphite 2.4:1, pH 3.4, reaction at 47℃ for 145 min, after removing the precipitate by precision membrane filtration, Bi≤0.0008 g / L, Sn≤0.0006 g / L, Pb≤0.0007 g / L.
[0104] S4. Electrolyte preparation: Electrolyte additives: modified chitosan 0.03 g / L, rare earth chloride (lanthanum chloride: cerium chloride = 3:2, mass ratio) 0.011 g / L, leveling agent 0.016 g / L, acidity 1.6 mol / L, 0.2 μm microfiltration.
[0105] S5. Electrolysis: Titanium-coated ruthenium anode, pure copper cathode, electrolysis electrode spacing 92 mm, temperature 44℃, current density 110 A / m², electrolysis for 25 h, continuous closed negative pressure bypass microfiltration circulation.
[0106] S6. Ultrasonic drying: Level 4 ultrasonic cleaning for 8 min, power 200 W, vacuum drying at 68℃ for 105 min.
[0107] S7. Residual liquid can be recycled with supplementary medication.
[0108] The test results showed that the finished product had a purity of 99.9991%, total impurities of 9.0 ppm, a maximum single impurity of 0.079 ppm, and a direct recovery rate of 96.5%.
[0109] Example 4 A method for preparing 5N grade copper raw materials by chemical reduction combined with electrolytic purification, comprising the following steps: S1. Preparation of crude copper acid leaching solution: 99.0% Cu crude copper anode material, 1.9 mol / L sulfuric acid, leaching at 69℃, liquid-to-solid ratio 6.2:1, stirring for 3.0 h; Cu²⁺ stock solution + 65g / L, Fe 0.13g / L, Sn 0.08g / L, Pb 0.09g / L, Bi 0.055g / L, Sb0.041g / L, As 0.13g / L, Ni 0.11g / L.
[0110] S2, First-stage reduction to remove arsenic and antimony: Sodium bisulfite ratio 2.1:1, pH 2.3, reaction at 43℃ for 132 min, filter press to remove residue, after filtration As and Sb ≤ 0.0015 g / L.
[0111] S3, Two-stage reduction: Sodium hypophosphite ratio 2.5:1, pH 3.5, reaction at 48℃ for 150 min, after precision membrane pressure filtration, Bi≤0.0008 g / L, Sn≤0.0006 g / L, Pb≤0.0006 g / L.
[0112] S4. Electrolyte preparation: modified chitosan 0.035 g / L, rare earth chloride (lanthanum chloride: cerium chloride = 3:2, mass ratio) 0.012 g / L, crystallization leveling agent 0.018 g / L, sulfuric acid 1.7 mol / L.
[0113] S5. Electrolysis: Titanium-coated ruthenium anode, pure copper cathode, electrolysis electrode distance 95 mm, constant temperature 45℃, current density 115 A / m², continuous electrolysis for 26 h.
[0114] S6. Ultrasonic drying: Ultrasonic cleaning single stage for 8 minutes, power 200W, vacuum drying at 70℃ for 110 minutes.
[0115] S7: Valuable metals are extracted from the reduction residue, and the electrolyte is recycled in a closed loop.
[0116] The results showed that the Cu purity was 99.9990%, the total impurities were 10 ppm, the highest single impurity was 0.082 ppm, and the direct recovery rate was 96.6%.
[0117] Example 5 A method for preparing 5N grade copper raw materials by chemical reduction combined with electrolytic purification, comprising the following steps: S1. Preparation of crude copper acid leaching solution: 99.1% Cu recycled crude copper, 1.95 mol / L sulfuric acid, leaching at 70℃, liquid-to-solid ratio 6.4:1, stirring for 3.1 h, resulting in a crude copper solution with Cu²⁺. + 66g / L, Fe 0.15g / L, Sn 0.09g / L, Pb 0.11g / L, Bi 0.068g / L, Sb0.050g / L, As 0.16g / L, Ni 0.13g / L.
[0118] S2, First stage reduction: Sodium bisulfite ratio 2.15:1, pH 2.4, reaction at 44℃ for 138 min, filter press to separate the reduction residue, after filtration, As and Sb ≤ 0.0015 g / L.
[0119] S3, Two-stage reduction of bismuth, tin and lead: Sodium hypophosphite 2.6:1, pH 3.6, reaction at 49℃ for 155 min, after precision membrane filtration, Bi≤0.0008 g / L, Sn≤0.0008 g / L, Pb≤0.0009 g / L.
[0120] S4. Electrolyte preparation: modified chitosan 0.04 g / L, rare earth chloride (lanthanum chloride: cerium chloride = 3:2, mass ratio) 0.013 g / L, crystallization leveling agent 0.019 g / L, acidity 1.75 mol / L.
[0121] S5. Electrolysis: Electrolysis electrode spacing 98 mm, temperature 46℃, current density 120 A / m², electrolysis for 28 h.
[0122] S6. Ultrasonic drying: single-stage ultrasonic drying for 9 minutes, power 210W, vacuum drying at 71℃ for 115 minutes.
[0123] S7: Residual liquid is recycled and replenished with chemicals.
[0124] The test results showed that the finished product had a purity of 99.9990%, total impurities of 10 ppm, a maximum single impurity of 0.078 ppm, and a direct recovery rate of 96.5%.
[0125] Example 6 A method for preparing 5N grade copper raw materials by chemical reduction combined with electrolytic purification, comprising the following steps: S1. Preparation of crude copper acid leaching solution: 99.2% Cu crude copper anode material, sulfuric acid 2.0 mol / L, leaching at 71℃, liquid-to-solid ratio 6.5:1, stirring for 3.2 h; Cu²⁺ stock solution + 68g / L, Fe 0.17g / L, Sn 0.11g / L, Pb 0.13g / L, Bi 0.075g / L, Sb0.062g / L, As 0.19g / L, Ni 0.14g / L.
[0126] S2, First-stage reduction to remove arsenic and antimony: Sodium bisulfite ratio 2.2:1, pH 2.5, reaction at 45℃ for 142 min, filter press to remove residue, after filtration As and Sb ≤ 0.0015 g / L.
[0127] S3, Two-stage reduction: Sodium hypophosphite 2.7:1, pH 3.7, reaction at 50℃ for 160 min, after precision membrane pressure filtration, Bi≤0.0008 g / L, Sn≤0.0008 g / L, Pb≤0.0008 g / L.
[0128] S4. Electrolyte preparation: Chitosan 0.045 g / L, rare earth chloride (lanthanum chloride:cerium chloride = 3:2, mass ratio) 0.014 g / L, crystallization leveling agent 0.020 g / L, sulfuric acid 1.8 mol / L.
[0129] S5. Electrolysis: Electrolysis electrode spacing 100 mm, constant temperature 46℃, current density 125 A / m², electrolysis for 29 h.
[0130] S6. Ultrasonic drying: Level 4 ultrasonic single-stage drying for 9 min, power 220W, vacuum drying at 72℃ for 120 min.
[0131] S7: Two-stage reduction slag recovers metal, and the electrolyte is recycled.
[0132] The results showed that Cu content was 99.9992%, total impurities were 8.0 ppm, the highest single impurity was 0.082 ppm, and the direct recovery rate was 96.7%.
[0133] Example 7 A method for preparing 5N grade copper raw materials by chemical reduction combined with electrolytic purification, comprising the following steps: S1. Preparation of crude copper acid leaching solution: 99.3% crude copper, 2.05 mol / L sulfuric acid, leaching temperature 72℃, liquid-to-solid ratio 6.6:1, stirring for 3.3 h, original solution Cu² + 69 g / L, Fe 0.18 g / L, Sn 0.12 g / L, Pb 0.14 g / L, Bi 0.082 g / L, Sb0.070 g / L, As 0.21 g / L, Ni 0.16 g / L.
[0134] S2, First stage reduction: Sodium bisulfite ratio 2.25:1, pH 2.6, reaction at 46℃ for 145 min, filter press to separate the first reduction residue, after filtration As and Sb ≤ 0.0015 g / L.
[0135] S3, Two-stage reduction: Sodium hypophosphite 2.8:1, pH 3.8, reaction at 51℃ for 163 min, after precision membrane filtration, Bi≤0.0008 g / L, Sn≤0.0009 g / L, Pb≤0.0008 g / L.
[0136] S4. Electrolyte preparation: modified chitosan 0.05 g / L, rare earth chloride (lanthanum chloride: cerium chloride = 3:2, mass ratio) 0.015 g / L, crystallization leveling agent 0.022 g / L, acidity 1.85 mol / L.
[0137] S5. Electrolysis: Electrolysis electrode distance 102 mm, temperature 47℃, current density 130 A / m², electrolysis for 30 h.
[0138] S6. Ultrasonic drying: Ultrasonic drying at single stage for 10 min, power 220 W, vacuum drying at 73℃ for 122 min.
[0139] S7: Residual liquid is returned to the electrolyte preparation process.
[0140] The test results showed that the purity of the finished product was 99.9992%, the total impurities were 8 ppm, all impurities were below 0.08 ppm, and the direct recovery rate was 96.8%.
[0141] Example 8 A method for preparing 5N grade copper raw materials by chemical reduction combined with electrolytic purification, comprising the following steps: S1. Preparation of crude copper acid leaching solution: 99.4% Cu recycled crude copper anode material, leaching at 73℃ with 2.1 mol / L sulfuric acid at a liquid-to-solid ratio of 6.8:1, stirred for 3.4 h; Cu²⁺ stock solution + 70g / L, Fe 0.20 g / L, Sn 0.13 g / L, Pb 0.16 g / L, Bi0.095 g / L, Sb 0.078 g / L, As 0.23 g / L, Ni 0.18 g / L.
[0142] S2, First-stage reduction to remove arsenic and antimony: Sodium bisulfite ratio 2.3:1, pH 2.7, reaction at 47℃ for 148 min, filter press to remove residue, after filtration As and Sb ≤ 0.0015 g / L.
[0143] S3, Two-stage reduction of bismuth, tin and lead: Sodium hypophosphite 2.9:1, pH 3.9, reaction at 52℃ for 166 min, after precision membrane pressure filtration, Bi≤0.0008 g / L, Sn≤0.0010 g / L, Pb≤0.0009 g / L.
[0144] S4. Electrolyte preparation: modified chitosan 0.055 g / L, rare earth chloride (lanthanum chloride: cerium chloride = 3:2, mass ratio) 0.016 g / L, crystallization leveling agent 0.023 g / L, sulfuric acid 1.9 mol / L.
[0145] S5. Electrolysis: Electrolysis electrode distance 103 mm, constant temperature 48℃, current density 135 A / m², electrolysis for 31 h.
[0146] S6. Ultrasonic drying: ultrasonic power 230W, single stage for 10 minutes, vacuum drying at 74℃ for 126 minutes.
[0147] S7: Resource recovery of reduction residue and closed-loop electrolyte.
[0148] Test results: Cu 99.9992%, total impurities 8 ppm, highest single impurity 0.068 ppm, copper direct recovery rate 96.8%.
[0149] Example 9 A method for preparing 5N grade copper raw materials by chemical reduction combined with electrolytic purification, comprising the following steps: S1. Preparation of crude copper acid leaching solution: 99.5% Cu crude copper anode material, sulfuric acid 2.2 mol / L, leaching at 75℃, liquid-to-solid ratio 7:1, stirring for 3.5 h, raw solution Cu² +72 g / L, Fe 0.22 g / L, Sn 0.15 g / L, Pb 0.18 g / L, Bi 0.11 g / L, Sb0.09 g / L, As 0.25 g / L, Ni 0.20 g / L.
[0150] S2, First stage reduction: Sodium bisulfite ratio 2.4:1, pH 2.8, reaction at 48℃ for 150 min, filter press to separate the reduction residue, after filtration, As and Sb ≤ 0.0015 g / L.
[0151] S3, Two-stage reduction: Sodium hypophosphite 3.0:1, pH 4.0, reaction at 53℃ for 170 min, after precision membrane filtration, Bi≤0.0008 g / L, Sn≤0.0006 g / L, Pb≤0.0007 g / L.
[0152] S4. Electrolyte preparation: modified chitosan 0.06 g / L, rare earth chloride (lanthanum chloride: cerium chloride = 3:2, mass ratio) 0.018 g / L, crystallization leveling agent 0.025 g / L, sulfuric acid 2.0 mol / L.
[0153] S5. Electrolysis: Electrolysis electrode distance 105 mm, constant temperature 50℃, current density 140 A / m², electrolysis for 32 h.
[0154] S6. Ultrasonic drying: Level 4 ultrasonic cleaning for 10 min, power 240 W, vacuum drying at 75℃ for 130 min.
[0155] S7: Residual liquid is replenished with chemicals for recycling.
[0156] Test results: The purity of the finished product is 99.9991%, the total impurities are 9.0 ppm, the highest single impurity is 0.075 ppm, no zone melting purification is required, and the direct recovery rate is 96.8%.
[0157] Example 10 This embodiment is basically the same as Embodiment 1, except that: S1. Preparation of crude copper acid dissolution stock solution: sulfuric acid 1.9 mol / L, leaching temperature 70℃, liquid-solid ratio 6:1, stirring for 3 h; S2, First stage reduction: The molar ratio of sodium bisulfite to As and Sb is 2.0:1, pH 2.4, reaction at 44℃ for 130 min; S3, Two-stage reduction: The molar ratio of sodium hypophosphite to Bi+Sn+Pb is 2.6:1, pH 3.6, reaction at 49℃ for 150 min; S4. Electrolyte preparation: chitosan concentration 0.04 g / L, rare earth chloride (lanthanum chloride: cerium chloride = 3:2, mass ratio) 0.012 g / L, crystallization leveling agent concentration 0.018 g / L; S5. Electrolysis: Electrode spacing 95mm, electrolyte temperature 45℃, current density 110 A / m 2 Electrolysis for 26 hours; S6. Ultrasonic drying: 200W ultrasonic power, single-stage ultrasonic for 8 minutes, vacuum drying at 70℃ for 110 minutes; no sulfurizing agents are used throughout the process, and the electrolyte is circulated.
[0158] The finished product has a Cu content of 99.9991%, total impurities of 9 ppm, a maximum single impurity of 0.077 ppm, and a direct recovery rate of 96.6%.
[0159] The main process parameters used in Examples 1-10, as well as the proportions of products and impurities, are shown in Table 1.
[0160] Table 1. Main process parameters used in Examples 1-10 and the proportions of products and impurities.
[0161] As can be seen from Table 1, the process effect of the present invention does not depend on a specific parameter point, but can stably achieve the purpose of the invention within the entire defined range, and the parameter window has sufficient margin. At the same time, the range of raw material grade from 98.5% to 99.5% indicates that the process has good adaptability to waste copper recycling raw materials of different grades, and there is no need to frequently adjust the process parameters due to raw material fluctuations. It has the robustness and feasibility of continuous industrial-scale production.
[0162] Example 11 This embodiment is basically the same as Embodiment 1, except that: The raw material contains 98.6% Cu, and the original solution obtained by pressure filtration contains Cu². + 56 g / L, impurities: Fe 0.08 g / L, Sn 0.02 g / L, Pb 0.04 g / L, Bi 0.013 g / L, Sb 0.012 g / L, As 0.04 g / L, Ni 0.04 g / L.
[0163] S2, First stage reduction: After pressure filtration, As and Sb ≤ 0.0015 g / L; S3, Two-stage reduction: After precision membrane filtration, Bi≤0.0008 g / L, Sn≤0.0007 g / L, Pb≤0.0008 g / L; S5: Electrolytic electrode spacing 100 mm, 48℃, 130A / m² electrolysis for 30 h; S6: Ultrasonic power 220 W, single stage 9 min, 72℃ drying 120 min.
[0164] After impurity removal, the finished product has a purity of 99.9990%, a total impurity of 10 ppm, a maximum single impurity of 0.075 ppm, and a direct recovery rate of 96.5%.
[0165] Example 12 This embodiment is basically the same as Embodiment 1, except that: S1: Raw material 98.8%, the original liquid obtained by pressure filtration contains Cu² + 57 g / L, impurities: Fe 0.08 g / L, Sn 0.03 g / L, Pb 0.03 g / L, Bi 0.015 g / L, Sb 0.018 g / L, As 0.05 g / L, Ni 0.08 g / L.
[0166] S2: The molar ratio of sodium bisulfite to As and Sb is 2.4:1, the reduction temperature is 48℃, the reaction time is 150 min, and after pressure filtration, As and Sb are ≤0.0015 g / L. S3: The molar ratio of sodium hypophosphite to Bi+Sn+Pb is 3.0:1, the reduction temperature is 53℃, the reaction time is 170 min, and after fine membrane filtration, Bi≤0.0008 g / L, Sn≤0.0007 g / L, and Pb≤0.0009 g / L. S4: In the electrolyte, modified chitosan 0.06 g / L, rare earth chloride (lanthanum chloride:cerium chloride = 3:2, mass ratio) 0.018 g / L; crystallization leveling agent 0.012 g / L, sulfuric acid acidity 1.4 mol / L.
[0167] S5: Current density 140 A / m², constant temperature 50℃, electrolysis for 32 h; The pretreatment impurity removal rate is still ≥99%, the total impurities in the finished product are 10ppm, the highest single impurity is 0.085ppm, the purity is 99.9990%, and the direct recovery rate is 96.5%.
[0168] Example 13 This embodiment is basically the same as embodiment 10, except that: S5: Electrolysis current density 90 A / m², constant temperature 42℃, electrolysis for 22 h; S6: Ultrasonic drying at 180 W for 6 min, followed by low-temperature vacuum drying at 65℃ for 90 min.
[0169] In this embodiment, the cathode copper is densely crystalline with no surface impurity particles, and has an oxygen content of 0.42 ppm, which meets the standards for semiconductor target materials. The Cu purity is 99.9993%, the total impurities are 7 ppm, the highest single impurity is 0.071 ppm, and the direct recovery rate is 96.8%.
[0170] Example 14 This embodiment is basically the same as embodiment 10, except that: The raw material is industrial waste copper pyrometallurgical rough casting anode; S5: Electrolysis current density 115 A / m², electrode spacing 95 mm, electrolyte bypass microfiltration continuous operation; The Cu purity is 99.9991%, with total impurities of 9 ppm and a maximum single impurity of 0.081 ppm. The direct recovery rate is 96.5%. Energy consumption per ton of copper is reduced by 28.1% compared to Comparative Example 5.
[0171] Example 15 This embodiment is basically the same as embodiment 10, except that: S4: Modified chitosan concentration 0.06 g / L, rare earth chloride concentration 0.018 g / L; S5: Electrolysis current density 140 A / m², constant temperature 50℃, electrolysis for 32 h; In this embodiment, the effect of suppressing Fe and Ni co-deposition is optimal, with only 0.068 ppm of single Ni impurity, no trace metal precipitation spots on the cathode, Cu purity of 99.9991%, total impurities of 9 ppm, single impurity of 0.079 ppm, and direct recovery rate of 96.6%.
[0172] Example 16 This embodiment is basically the same as embodiment 10, except that: S4: Rare earth chloride lanthanum cerium mass ratio 3:2, total concentration 0.013 g / L.
[0173] The product has a Cu purity of 99.9991%, total impurities of 9 ppm, a single impurity of up to 0.080 ppm, and a direct recovery rate of 96.5%.
[0174] Compared with Comparative Example 1, the removal of Fe impurities in this example was improved by 21%, and the amount of suspended anode mud in the electrolyte was reduced by 65%.
[0175] The main process parameters used in Examples 11-16, as well as the proportions of products and impurities, are shown in Table 2.
[0176] Table 2. Main process parameters used in Examples 11-16 and the percentages of products and impurities.
[0177] As shown in Table 2, Examples 11-16 were verified one by one for various scenarios, including raw material grade fluctuations, the superposition of the upper limit of the parameter range and high-impurity raw materials, electrolysis and washing lower limit conditions, another type of recycled raw materials, enhanced combination of additives and electrolysis conditions, and specific ratios of rare earth components. The purity of the finished products in all examples was not less than 99.9990%, stably meeting the 5N grade copper raw material index. This indicates that the process of the present invention has a stable ability to meet the standards under the upper and lower limits of the parameter range and various boundary conditions, and has a wide adaptability to raw material sources and composition fluctuations.
[0178] Comparative Example 1 This comparative example is basically the same as Example 10, except that: It does not contain rare earth chlorides.
[0179] In this comparative example: during the electrolysis process, the anode mud was in a loose and dispersed state and settled slowly. The turbidity of the electrolyte increased with the running time and the number of suspended particles increased. The copper content in the product was 99.9982%, of which the Bi content was 0.0008%. The highest single impurity was 8 ppm and the total impurities were 12 ppm, which did not meet the 5N requirement.
[0180] As can be seen from Comparative Example 1, since no rare earth chlorides are added to the electrolyte, the morphology of the anode mud is not controlled: the anode mud particles cannot be densified and settle quickly, and drift in the electrolyte in a loose suspended state. They are attached to the cathode deposited layer with the convection of the electrolyte and mixed in the cathode deposited layer. The bismuth and other impurity elements enriched in the anode mud enter the cathode, resulting in a high Bi single impurity in the product.
[0181] Comparative Example 2 This comparative example is basically the same as Example 10, except that: It does not contain modified chitosan.
[0182] The copper content in this comparative product is 99.9979%, with Ni impurities of 7 ppm, Fe impurities of 0.16 ppm, and total impurities of 15.3 ppm, which does not meet the 5N requirement.
[0183] As can be seen from Comparative Example 2, because no modified chitosan was added to the electrolyte, Fe 2+ Ni 2+ Without the inhibitory mechanism of selective complexation, Ni 2+ and Fe 2+ The Ni impurities are deposited along with the copper into the cathode, resulting in a final product with a single impurity content of 0.0007%.
[0184] Comparative Example 3 This comparative example omits the two-stage stepwise reduction and uses sodium sulfide, pH 2.0, and a reaction at 40°C for 120 min for pretreatment. The remaining processes are the same as in Example 10.
[0185] In this comparative example, the removal rates of As and Sb were only 76%, the Bi content was 3 ppm, the Sn content was 5 ppm, the Pb content was 5 ppm, the highest single impurity was 5 ppm, the total impurities in the finished product were 16.8 ppm, and hydrogen sulfide waste gas was generated. The copper entrainment loss was 3.2%, and the copper content in the product was 99.997%. This verifies that the segmented reduction method has significant technical advantages over the simultaneous sulfidation method.
[0186] Comparative Example 4 This comparative example is basically the same as Example 1, except that: The two reductions were carried out simultaneously: sodium bisulfite and sodium hypophosphite were added to the crude copper acid solution, the concentration of the crude copper acid solution was 1.6 mol / L, and the reaction was carried out at pH 1.5 and 45℃ for 2.5 hours.
[0187] After reduction, precision membrane filtration was performed, and the filtrate contained 12 ppm of As, 6 ppm of Sb, 2 ppm of Bi, 5 ppm of Sn, and 6 ppm of Pb.
[0188] The copper content in this comparative product is 99.9970%, with As content of 0.0007%, a maximum single impurity of 7 ppm, and a total impurity of 30 ppm, which does not meet the 5N requirement.
[0189] As can be seen from Comparative Example 4, the reducing agents used in the two reductions in this application have different required temperatures and pH windows, resulting in the destruction of selectivity: the reducing agent and the precipitation reaction compete with each other, and the two types of precipitates are generated simultaneously and encapsulate each other, resulting in incomplete removal of arsenic and antimony as well as bismuth, tin and lead. The residual impurities enter the electrolysis process and are co-deposited at the cathode, resulting in insufficient product purity.
[0190] Comparative Example 5 The raw materials used in this comparative example are basically the same as those in Example 1, except that: The selective reduction pretreatments in stages S2 and S3 were cancelled. The crude copper acid solution obtained in S1 was directly used as the base electrolyte. A composite selective additive was added to prepare a composite electrolyte. The rest of the process was the same as in Example 1.
[0191] The copper content in this comparative product is 99.9960%, including 0.0012% As, 0.0004% Sb, 0.0005% Bi, 0.0006% Sn, and 0.0007% Pb. The highest single impurity is 12 ppm, and the total impurities are 40 ppm, which does not meet the 5N requirement.
[0192] As can be seen from Comparative Example 5, the two-stage selective reduction pretreatment is a crucial step in the deep removal of arsenic, antimony, bismuth, tin, and lead before electrolysis. Without this pretreatment, the five types of impurities in the raw solution enter the electrolyte without any reduction precipitation. During electrolysis, they co-deposit with copper at the cathode. Arsenic, with a deposition potential close to that of copper, exhibits the strongest co-deposition tendency, resulting in a significant exceedance of the arsenic single-impurity limit in the finished product. Furthermore, impurity ions continuously accumulate with electrolyte circulation. The composite selective additive has no ability to remove these impurities, thus the product purity is lower than that of Comparative Examples 3 and 4. This demonstrates that the two-stage selective reduction pretreatment is neither optional nor can it be simplified to other forms of simultaneous treatment.
[0193] Comparative Example 6 This comparative example is basically the same as Example 10, except that: It does not contain crystallizing leveling agents.
[0194] During the electrolysis process, the cathode deposit layer loses its leveling control, resulting in loose crystals and pinhole-like defects on the surface. The product contains 99.9978% copper, 0.0008% sulfur, a maximum of 8 ppm for single impurities, and 22 ppm for total impurities, which does not meet the 5N requirement.
[0195] As can be seen from Comparative Example 6, due to the absence of a crystallization leveling agent in the electrolyte, the leveling mechanism of the cathode deposition layer is missing, the cathode crystals are coarsened, loose, and pinhole-like defects are generated. The electrolyte (copper sulfate system, containing a large amount of sulfate) is retained in the pinholes and loose grain boundaries and enters the finished product along with the deposition layer, resulting in a high sulfur content.
[0196] Comparative Example 7 This comparative example is basically the same as Example 10, except that: The rare earth chloride is lanthanum chloride.
[0197] In this comparative example: during the electrolysis process, the density of the anode mud was not as high as in Example 10, the settling rate was lower than in Example 10, the electrolyte showed moderate turbidity, the turbidity increased slowly with running time, and the copper content in the final product was 99.9985%, the highest single impurity was 7 ppm, and the total impurities were 15 ppm, which did not meet the 5N requirement.
[0198] As can be seen from Comparative Example 7, the ability of lanthanum chloride alone to control the morphology of anode mud is insufficient.
[0199] Comparative Example 8 This comparative example is basically the same as Example 10, except that: Rare earth chlorides are only cerium chloride.
[0200] In this comparative example: during the electrolysis process, the anode mud was in a loose and dispersed state and settled slowly. The electrolyte gradually became turbid and the turbidity continued to rise as the running time increased, and the amount of residue retained by the bypass microfiltration membrane increased. The concentration of cerium ions in the circulating electrolyte decreased slowly. Sporadic particle inclusions appeared on the surface of the cathode deposit layer and the roughness increased. The copper content in the product was 99.9986%, the highest single impurity was 7 ppm, and the total impurities were 14 ppm, which did not meet the 5N requirement.
[0201] As can be seen from Comparative Example 8, when cerium chloride is used alone, due to the continuous oxygen evolution at the anode, the tank is in a strong oxidizing atmosphere, and Ce... 3+ Partially oxidized to Ce 4+ And Ce 4+ In the sulfuric acid system, it is very easy to hydrolyze to form basic cerium sulfate / cerium dioxide and other insoluble substances. On the one hand, it consumes the effective concentration of rare earth elements that should have participated in the morphology control of anode mud. On the other hand, the newly generated cerium-based precipitate particles themselves become new sources of suspended pollution, resulting in loose anode mud, turbid electrolyte and inclusion on the cathode surface.
[0202] Comparative Example 9 This comparative example is basically the same as Example 10, except that: Chitosan was not modified.
[0203] In this comparative example: during the electrolyte preparation stage, after the chitosan was added to the electrolyte, it dissolved slowly and appeared as swollen particles or flocculent suspensions. The clarity of the solution was lower than that of the modified chitosan system. The copper content in the product was 99.9981%, of which the Fe content was 0.0006%. The highest single impurity was 9 ppm, and the total impurities were 19 ppm, which did not meet the 5N requirement.
[0204] As can be seen from Comparative Example 9, because chitosan was not modified, its dissolution rate was slow, and it existed in a swollen particle or flocculent suspension state, resulting in a small effective complexation area, reduced complexation ability and selectivity, and thus reduced Fe... 2+ Ni 2+ Co-deposition at the cathode resulted in the product purity not meeting the 5N requirement.
[0205] Comparative Example 10 This comparative example is basically the same as Example 10, except that: S5: Electrode spacing 95 mm, electrolyte temperature 45℃, current density 160 A / m², electrolysis for 26 h.
[0206] In this comparative example: during the electrolysis process, the current density on the cathode surface increases and the deposition rate accelerates significantly. However, dark spots and rough protrusions gradually appear on the cathode surface, the density of the deposition layer decreases, and dendritic and needle-like crystals appear locally.
[0207] The product of this comparative example contains 99.9976% copper, with 5 ppm Fe and 8 ppm Ni. The highest single impurity is 10 ppm, and the total impurities are 24 ppm, which does not meet the 5N requirement.
[0208] As can be seen from this comparative example, when the current density exceeds 140 A / m², the cathode polarization increases and the overpotential rises, reaching the Fe... 2+ Ni 2+ The deposition overpotential of Fe 2+ Ni 2+ It begins to compete with copper for discharge; at the same time, concentration polarization intensifies under high current density, and the mass transfer flux of impurity ions to the cathode increases synchronously, further amplifying co-deposition, ultimately leading to excessive Fe and Ni single impurities in the finished product.
[0209] Comparative Example 11 This comparative example is basically the same as Example 10, except that: S5: Electrode spacing 95 mm, electrolyte temperature 45℃, current density 70 A / m², electrolysis for 26 h.
[0210] In this comparative example: during the electrolysis process, the deposition rate slowed down significantly, the cathode copper deposition layer thickness was insufficient within the same electrolysis time, and the output per cell decreased.
[0211] The product of this comparative example has a copper content of 99.9982%, with Fe content of 3 ppm, Ni content of 7 ppm, a maximum single impurity of 8 ppm, and a total impurity of 18 ppm, which does not meet the 5N requirement.
[0212] Comparative Example 12 This comparative example is basically the same as Example 10, except that: S2: The molar ratio of sodium bisulfite to As and Sb is 1.5:1, pH 2.4, and the reaction is carried out at 44℃ for 130 min.
[0213] In this comparative example: the residual As in the filtrate after S2 was 0.002 g / L and the residual Sb was 0.003 g / L. The copper content in the product was 99.9975%. The highest single impurity was 10 ppm and the total impurities were 25 ppm, which did not meet the 5N requirement.
[0214] As can be seen from this comparative example, when the amount of sodium bisulfite is low, the reducing power is insufficient to fully convert As(V) and Sb(V). The unconverted portion remains in the filtrate in ionic form and enters the electrolysis process, where it is co-deposited at the cathode.
[0215] Comparative Example 13 This comparative example is basically the same as Example 10, except that: S2: The molar ratio of sodium bisulfite to As and Sb is 2.6:1, pH 2.4, and the reaction is carried out at 44℃ for 130 min.
[0216] In this comparative example: the residual As and Sb in the filtrate after S2 were low, ≤0.0015 g / L, but copper powder appeared in the reduction residue, and Cu in the filtrate... + With increased concentration, the purity of the finished copper is 99.9992%, with a maximum single impurity of 0.080 ppm and a total impurity of 8 ppm, which still meets the 5N requirement, but the direct copper recovery rate drops to 92.7%.
[0217] As can be seen from this comparative example, when the amount of sodium bisulfite is high, the reducing effect of excess sodium bisulfite is no longer limited to As(V) and Sb(V), but also begins to simultaneously reduce Cu in the solution. 2+ Cu 2+ Reduced to Cu + Even copper powder can enter the reducing slag, causing a decrease in the direct recovery rate of copper.
[0218] Comparative Example 14 This comparative example is basically the same as Example 10, except that: S3: The molar ratio of sodium hypophosphite to Bi+Sn+Pb is 2.0:1 (below the lower limit of 2.2:1), pH 3.6, reaction at 49℃ for 150 min.
[0219] In this comparative example: the residual Bi in the S3 post-filtrate was 0.005 g / L, the residual Sn was 0.020 g / L, and the residual Pb was 0.025 g / L, which is relatively high. The copper content in the product was 99.9973%, the highest single impurity was 8 ppm, and the total impurities were 27 ppm, which does not meet the 5N requirement.
[0220] As can be seen from this comparative example, when the amount of sodium hypophosphite is low, its precipitation ability is insufficient to cause Bi to precipitate. 3+ Sn 2+ / Sn 4+ Pb 2+ Complete conversion occurs, while the unconverted portion remains in the filtrate in ionic form and enters the electrolysis process, where it is co-deposited at the cathode.
[0221] Comparative Example 15 This comparative example is basically the same as Example 10, except that: S3: The molar ratio of sodium hypophosphite to Bi+Sn+Pb is 3.5:1, pH 3.6, and the reaction is carried out at 49℃ for 150 min.
[0222] The copper content in this comparative product is 99.9986%, with a relatively high P content of 3 ppm, a maximum single impurity of 5 ppm, and a total impurity of 14 ppm, which does not meet the 5N requirement.
[0223] As can be seen from this comparative example, when the amount of sodium hypophosphite is high, the residual Bi, Sn, and Pb in the filtrate after the S3 reaction meet the standards, but the phosphorus content in the filtrate increases significantly and the phosphorus element continues to accumulate in the electrolyte, which reduces the purity of the finished copper.
[0224] Comparative Example 16 This comparative example is basically the same as Example 10, except that: S4: Rare earth chloride is a mixture of lanthanum chloride and cerium chloride, with a mass ratio of lanthanum chloride to cerium chloride of 1:2 and a total rare earth concentration of 0.012 g / L.
[0225] In this comparative example: during the electrolysis process, the mud layer on the anode surface is densely accumulated and is not easily peeled off with the flow of electrolyte. The mud layer on the anode side gradually thickens. The copper content in the product is 99.9983%, the highest single impurity is 5 ppm, and the total impurities are 17 ppm, which does not meet the 5N requirement.
[0226] As can be seen from this comparative example, the proportion of lanthanum in the rare earth system is insufficient, the anode mud is excessively dense and accumulates on the anode surface, blocking the oxygen evolution channel and reducing the purity of the final product.
[0227] Comparative Example 17 This comparative example is basically the same as Example 10, except that: S4: Rare earth chloride is a mixture of lanthanum chloride and cerium chloride, with a mass ratio of lanthanum chloride to cerium chloride of 5:2 and a total rare earth concentration of 0.012 g / L.
[0228] In this comparative example: during the electrolysis process, the anode mud was excessively dispersed, the electrolyte was in a suspended and turbid state, the turbidity increased with the running time, the bypass microfiltration membrane retained more material, the copper content in the product was 99.9984%, the Bi content was 0.0006%, the highest single impurity was 6 ppm, and the total impurities were 16 ppm, which did not meet the 5N requirement.
[0229] As can be seen from this comparative example, when the proportion of lanthanum is too high, the auxiliary regulatory effect of cerium is relatively weakened. The anode mud particles are excessively refined and difficult to aggregate and settle. They drift in the electrolyte in a suspended state for a long time, bringing the impurity elements they have accumulated into the finished product, resulting in a decrease in the purity of the final product.
[0230] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing 5N grade copper raw materials through chemical reduction combined with electrolytic purification, characterized in that, Includes the following steps: S1. Acid dissolution of crude copper: Take recycled crude copper anode material, leach it with dilute sulfuric acid, and separate the solid and liquid to obtain crude copper acid dissolution stock solution; S2, First stage selective reduction: Sulfite reducing agent is added to the crude copper acid solution to react, solid-liquid separation is performed, and arsenic and antimony are removed; S3, Second stage selective reduction: Add hypophosphite reducing agent to the filtrate obtained in S2 to react, separate solid and liquid, and remove bismuth, tin and lead; S4. Electrolyte preparation: Take the filtrate obtained in S3 as the base electrolyte, add composite selective additives to obtain composite electrolyte; The composite selective additive comprises modified chitosan, rare earth chloride, and crystallization leveling agent; S5. Low-temperature, low-current electrolysis: using an insoluble anode, a pure copper cathode, and a composite electrolyte prepared in S4, at a current density of 90–140 A / m. 2 Electrolysis is performed at a temperature of 42–50℃, and the composite electrolyte is circulated through microfiltration. S6. Ultrasonic washing and drying: The cathode copper obtained by electrolysis is ultrasonically washed with multi-stage ultrapure water and then vacuum dried to obtain the 5N grade copper raw material.
2. The method according to claim 1, characterized in that, In S1, the recycled crude copper anode material is a pyrometallurgical rough casting anode made from scrap copper or intermediate crude copper material from copper smelting, with a Cu mass fraction of 98.5% to 99.5%.
3. The method according to claim 1, characterized in that, In S1, the concentration of the dilute sulfuric acid is 1.6–2.2 mol / L; And / or, the liquid-to-solid ratio of dilute sulfuric acid to recycled crude copper anode material is 5.5:1 to 7:1; And / or, the leaching temperature is 65–75°C.
4. The method according to claim 1, characterized in that, In S2, the molar ratio of the sulfite reducing agent to As and Sb in the crude copper acid solution is 1.8:1 to 2.4:
1. In S3, the molar ratio of the hypophosphite reducing agent to Bi, Sn, and Pb in the filtrate obtained in S2 is 2.2:1 to 3.0:
1.
5. The method according to claim 1, characterized in that, In S2, the reaction temperature is 40–48℃ and the pH is 2.0–2.8; In S3, the reaction temperature is 45–53℃ and the pH is 3.2–4.
0.
6. The method according to claim 1, characterized in that, In S4, the modified chitosan is carboxymethyl chitosan; And / or, the rare earth chloride is a mixture of lanthanum chloride and cerium chloride; the mass ratio of lanthanum chloride to cerium chloride is 2~4:2; And / or, the crystallization leveling agent is a mixture of an organic sulfonate containing thiol groups and / or disulfide bonds and low molecular weight gelatin.
7. The method according to claim 1, characterized in that, In the electrolyte, the concentration of the modified chitosan is 0.02–0.06 g / L; the concentration of the rare earth chloride is 0.008–0.018 g / L; and the concentration of the crystallization leveling agent is 0.012–0.025 g / L.
8. The method according to claim 1, characterized in that, In S5, the electrolysis time is 22–32 h, and the distance between the anode and cathode is 85–105 mm.
9. The method according to claim 1, characterized in that, In S5, the electrolyte is circulated through a bypass 0.2 μm microfiltration system; after electrolysis, the residual electrolyte is replenished with sulfuric acid and a composite selective additive and then returned to S4 for reuse.
10. The method according to claim 1, characterized in that, The 5N grade copper raw material has a Cu purity ≥ 99.999%, a total impurity content ≤ 10 ppm, a single impurity content of Fe, Sn, Pb, Bi, Sb, As, and Ni ≤ 0.09 ppm, an oxygen content ≤ 0.5 ppm, and a copper direct recovery rate ≥ 96.2%.
Citation Information
Patent Citations
5N high-purity copper production method
CN111378991A